Pendugaan Parameter Genetik, Korelasi, dan Klasterisasi 20 Genotipe Jarak Pagar (Jatropha curcas L.) - Edi Wardiana; Dibyo Pranowo (Buletin Plasma Nutfah, 2011)
Estimation of Genetic Parameters, Correlation, and Clusterization of Twenty Genotypes of Physic Nut (Jatropha curcas L.). This experiment was conducted at Pakuwon Experimental Station with altitude about 450 m above sea level, Latosol type of soil, and B type of climate, beginning from May 2008 until December 2009. It was aimed to analyze the genetic parameter, correlation, and clusterization of twenty genotypes of physic nut. Randomized complete block design with twenty genotypes of physic nut as treatment and three replications was used in this study. Variable observed were vegetative, generative, and yield characters, and the data observed were analyzed by anova, correlation, factor analyses, and cluster analyses. Results showed that : (1) the genetic variability of number of inflorescence/tree, number of bunchs/branch, number of bunch/tree, number of fruit harvested/tree, and weight of one fruit were narrow. Heritability and genetic advanced of these characters were rather high until high. Selection of these characters can be effective; (2) genotypic and phenotypic correlation of number of inflorescense/tree, number of bunch/branch, and number of bunch/tree were positive significant on number of fruit harvested. Phenotypically, plant height were positive correlated and number of primary branch/tree was negative correlated on number of fruits harvested; and (3) clusterizaton results six clusters. Rescaled distance between cluster I, II, and IV were rather near, whereas between cluster III, V, and VI were rather far as well as if compared to cluser I, II, and IV. AbstrakPenelitian dilakukan di KP Pakuwon, Jawa Barat, pada ketinggian tempat sekitar 450 m dpl, jenis tanah Latosol dan tipe iklim B, pada bulan Mei 2008 sampai Desember 2009. Tujuan penelitian adalah untuk menganalisis parameter genetik, korelasi, dan klasterisasi 20 genotipe jarak pagar. Rancangan yang digunakan adalah acak kelompok lengkap dengan 20 genotipe sebagai perlakuan yang diulang tiga kali. Peubah yang diukur meliputi karakter vegetatif, generatif, dan hasil. Analisis data dilakukan melalui analisis ragam, analisis korelasi, analisis faktor, dan analisis klaster. Hasil penelitian menunjukkan bahwa (1) Jumlah infloresen/pohon, jumlah tandan buah/cabang, jumlah tandan buah/pohon, jumlah buah panen/ pohon, dan bobot satu butir buah memiliki variabilitas genetik yang luas dengan nilai heritabilitas dan kemajuan genetik yang cukup tinggi sampai tinggi. Seleksi terhadap karakter-karakter tersebut akan efektif. (2) Karakter jumlah infloresen/ pohon, jumlah tandan buah/cabang, dan jumlah tandan buah/ pohon berkorelasi positif dengan jumlah buah panen, baik secara genotipik maupun fenotipik. Secara fenotipik, tinggi tanaman berkorelasi positif dan jumlah cabang primer/pohon berkorelasi negatif dengan jumlah buah panen. (3) Klasterisasi menghasilkan enam klaster. Antara klaster I, II, dan IV mempunyai jarak yang agak dekat, sedangkan antara klaster III, V, dan VI agak jauh, demikian juga antara klaster I, II, dan IV.